2018
DOI: 10.1016/j.bcp.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

A timeline of hydrogen sulfide (H2S) research: From environmental toxin to biological mediator

Abstract: The history of HS - as an environmental toxin - dates back to 1700, to the observations of the Italian physician Bernardino Ramazzini, whose book "De Morbis Artificum Diatriba" described the painful eye irritation and inflammation of "sewer gas" in sewer workers. The gas has subsequently been identified as hydrogen sulfide (HS), and opened three centuries of research into the biological roles of HS. The current article highlights the key discoveries in the field of HS research, including (a) the toxicological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
149
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(156 citation statements)
references
References 201 publications
2
149
0
5
Order By: Relevance
“…Basic sulfur salts, the so-called sulfide generators, showed initial promise as putative therapies [15], with efficacy demonstrated in several preclinical ischemia/reperfusion rodent models [17][18][19]. However, upon dissolution, these basic salts release all of their sulfur as sulfide in a near-instantaneous fashion with resulting implications for safety and efficacy [40].…”
Section: Discussionmentioning
confidence: 99%
“…Basic sulfur salts, the so-called sulfide generators, showed initial promise as putative therapies [15], with efficacy demonstrated in several preclinical ischemia/reperfusion rodent models [17][18][19]. However, upon dissolution, these basic salts release all of their sulfur as sulfide in a near-instantaneous fashion with resulting implications for safety and efficacy [40].…”
Section: Discussionmentioning
confidence: 99%
“…6 Risk estimate for the increment of 10 g dietary fibers per day. 7 Risk estimate for the increment of 25 g red and processed meat per day. 8 Risk estimate for the increment of 1 kJ energy per day (incl alcohol).…”
Section: Statisticsmentioning
confidence: 99%
“…Epidemiological studies suggest that high intake of red and particularly processed meat may increase the CRC risk [3], whereas long-term use of non-steroid anti-inflammatory drugs (NSAIDs) including aspirin (acetylic acid) may reduce the risk of CRC [4,5]. Investigations on the potential carcinogenic mechanisms of red and processed meat have suggested that meat may confer carcinogenesis by being a source of cooking mutations (heterocyclic amine, N-nitroso compounds) formed during preparation [6], organic sulfur-containing proteins leading to a high content of H 2 S in the intestinal lumen, a highly potent regulator of intestinal cell function including inflammation and cell death signaling [7] and/or microbial factors arising during storage [8]. Similarly, the underlying cancer protective mechanisms of NSAID have been investigated and both COX-2 dependent and COX-2 independent mechanisms have been suggested [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…H 2 S, previously regarded primarily as an environmental hazard and toxic gas, has recently been recognized as the third gasotransmitter after carbon monoxide (CO) and nitric oxide (NO; Szabo, ). H 2 S has become a focus of researches because of its role in various biological processes, such as neuronal health (Paul & Snyder, ), cardiovascular health, immune response (Yuan, Shen, & Kevil, ), and inflammation (Luo et al, ).…”
Section: Introductionmentioning
confidence: 99%